Efek Berganda Demokrasi pada Daya Saing Jawa Barat The Multiplier Effect of Democracy Effects on The West Java Competitiveness Index - Aurelia, Florence (Jurnal Global Ilmiah, 2025)
The Regional Competitiveness Index is an important instrument in forming the National Competitiveness Index. Referring to data from the Central Statistics Agency, several pillars of the West Java competitiveness index are still below the average of the National Competitiveness Index. This study aims to test the correlation between the dimensions of the Indonesian Democracy Index as an independent variable and the dimensions of the West Java competitiveness index as a dependent variable using a descriptive quantitative research method. The results of this study indicate the significance of several dimensions of the Regional Competitiveness Index and the dimensions of the Indonesian Competitiveness Index in analyzing the factual conditions of West Java.